A mechanism of global gene expression regulation is disrupted by multiple disease states and drug treatments - Benjamin S. Pickard (PLoS ONE, 2025)
Conventional expression studies quantify messenger RNA (mRNA) transcript levels gene-by-gene. We recently showed that protein expression is modulated at a global scale by amino acid availability, suggesting that mRNA expression levels might be equivalently affected. Through re-analysis of public transcriptomic datasets, it was confirmed that nucleobase supply interacts with the specific demands of mRNA A + U:C + G sequence composition to shape a global profile of expression, which can be quantified as a gradient of average expression change by average composition change. In mammals, each separate organ and cell-type displays a distinct baseline profile of global expression. These profiles can shift dynamically across the circadian day and the menstrual cycle. They are also significantly distorted by viral infection, multiple complex genetic disorders (including Alzheimer’s disease, schizophrenia, and autoimmune disorders), and after treatment with 115 of the 597 chemical entities analysed. These included known toxins and nucleobase analogues, but also many commonly prescribed medications such as antibiotics and proton pump inhibitors, thus revealing a new mechanism of drug action and side-effect. As well as key roles in disease susceptibility, mRNAs with extreme compositions are significantly over-represented in gene ontologies such as transcription and cell division, making these processes particularly sensitive to swings in global expression. This may permit efficient, en bloc transcriptional reprogramming of cell state through simple adjustment of nucleobase proportion and supply. It is also proposed that this mechanism helped mitigate the loss of essential amino acid synthesis in higher organisms. In summary, global expression regulation is invisible to conventional transcriptomic analysis, but its measurement allows a useful distinction between active, promoter-mediated gene expression changes and passive, cell state-dependent transcriptional competence. Linking cell metabolism directly to gene expression offers an entirely new perspective on evolution, disease aetiopathology (including gene x environment - GxE - interactions), and the nature of the pharmacological response.